Mapping twentieth-century history: PhD theses defended between 2010 and 2018 in Portugal - Rezola, Maria Inácia (2020)
In Portugal, twentieth-century history has benefited from greater public visibility and recognition, boosting the publishing industry and enjoying a regular presence in the media. Despite this popularity, little attention has been paid to the dynamics of history teaching and research at higher education institutions, especially at the PhD level. This article attempts to provide a broad overview of the PhD dissertations defended at Portuguese universities between 2010 and 2018. Presented under the scope of the considerable number of PhD programs offered by different universities, these theses are characterized by the diversity of the methods applied, the different areas of expertise and the range of topics covered. Despite the limitations of our inquiry, we hope to present some clues for a broader and deeper understanding of recent trends in Portuguese historiography.